Adult Hip Flexion Contracture due to Neurological Disease: A New Treatment Protocol—Surgical Treatment of Neurological Hip Flexion Contracture - Alberto Nicodemo; Chiara Arrigoni; Andrea Bersano; Alessandro Massè (Case Reports in Medicine)
Congenital, traumatic, or extrinsic causes can lead people to paraplegia; some of these are potentially; reversible and others are not. Paraplegia can couse hip flexion contracture and, consequently, pressure sores, scoliosis, and hyperlordosis; lumbar and groin pain are strictly correlated. Scientific literature contains many studies about children hip flexion related to neurological diseases, mainly caused by cerebral palsy; only few papers focus on this complication in adults. In this study we report our experience on surgical treatment of adult hip flexion contracture due to neurological diseases; we have tried to outline an algorithm to choose the best treatment avoiding useless or too aggressive therapies. We present 5 cases of adult hips flexion due to neurological conditions treated following our algorithm. At 1-year-follow-up all patients had a good clinical outcome in terms of hip range of motion, pain and recovery of walking if possible. In conclusion we think that this algorithm could be a good guideline to treat these complex cases even if we need to treat more patients to confirm this theory. We believe also that postoperation physiotherapy it is useful in hip motility preservation, improvement of muscular function, and walking ability recovery when possible.